Increased susceptibility of Trpv4-deficient mice to obesity and obesity-induced osteoarthritis with very high-fat diet. Issue 2 (23rd November 2012) - O'Conor, Christopher J; Griffin, Timothy M; Liedtke, Wolfgang; Guilak, Farshid
Abstract : Objective: To test the hypotheses that: (1) the transient receptor potential vanilloid 4 (TRPV4) ion channel is protective in the obesity model of osteoarthritis (OA), resulting in more severe obesity-induced OA in Trpv4 knockout ( Trpv4 −/− ) mice; and (2) loss of TRPV4 alters mesodermal stem cell differentiation. Methods: Male Trpv4 −/− and wild-type ( Trpv4 +/+ ) mice were fed a control or high-fat diet (10% kcal and 60% kcal from fat, respectively) for 22 weeks, at which time spontaneous cage activity and severity of knee OA were evaluated. In addition, the adipogenic, osteogenic and chondrogenic potential of bone marrow-derived (MSC) and adipose-derived (ASC) stem cells from Trpv4 −/− and Trpv4 +/+ mice were compared. Results: A high-fat diet significantly increased knee OA scores and reduced spontaneous cage activity in Trpv4 −/− mice, while also increasing weight gain and adiposity. MSCs from Trpv4 −/− mice had decreased adipogenic and osteogenic differentiation potential versus Trpv4 +/+ MSCs. ASCs from Trpv4 −/− mice had increased adipogenic and osteogenic and reduced chondrogenic differentiation potential versus Trpv4 +/+ ASCs. Conclusions: Pan- Trpv4 −/− mice develop more severe OA with high-fat feeding, potentially due to more severe diet-induced obesity. The altered differentiation potential of Trpv4 −/− progenitor cells may reflect the importance of this ion channel in the maintenance and turnover of mesodermally-derived tissues.